Astrocyte production of the chemokine macrophage inflammatory protein-2 is inhibited by the spice principle curcumin at the level of gene transcription - Santoro Thomas J; Holman Brita J; Santoro Christopher P; Tomita Michiyo (Journal of Neuroinflammation, 2005)
Abstract Background In neuropathological processes associated with neutrophilic infiltrates, such as experimental allergic encephalitis and traumatic injury of the brain, the CXC chemokine, macrophage inflammatory protein-2 (MIP-2) is thought to play a pivotal role in the induction and perpetuation of inflammation in the central nervous system (CNS). The origin of MIP-2 in inflammatory disorders of the brain has not been fully defined but astrocytes appear to be a dominant source of this chemokine. Curcumin is a spice principle in, and constitutes approximately 4 percent of, turmeric. Curcumin's immunomodulating and antioxidant activities suggest that it might be a useful adjunct in the treatment of neurodegenerative illnesses characterized by inflammation. Relatively unexplored, but relevant to its potential therapeutic efficacy in neuroinflammatory syndromes is the effect of curcumin on chemokine production. To examine the possibility that curcumin may influence CNS inflammation by mechanisms distinct from its known anti-oxidant activities, we studied the effect of this spice principle on the synthesis of MIP-2 by astrocytes. Methods Primary astrocytes were prepared from neonatal brains of CBA/CaJ mice. The cells were stimulated with lipopolysaccharide in the presence or absence of various amount of curcumin or epigallocatechin gallate. MIP-2 mRNA was analyzed using semi-quantitative PCR and MIP-2 protein production in the culture supernatants was quantified by ELISA. Astrocytes were transfected with a MIP-2 promoter construct, pGL3-MIP-2, and stimulated with lipopolysaccharide in the presence or absence of curcumin. Results The induction of MIP-2 gene expression and the production of MIP-2 protein were inhibited by curcumin. Curcumin also inhibited lipopolysaccharide-induced transcription of the MIP-2 promoter reporter gene construct in primary astrocytes. However MIP-2 gene induction by lipopolysaccharide was not inhibited by another anti-oxidant, epigallocatechin gallate. Conclusion Our results indicate that curcumin potently inhibits MIP-2 production at the level of gene transcription and offer further support for its potential use in the treatment of inflammatory conditions of the CNS.